Mangrove dynamics of Marapanim-PA in millennial, secular and decadal scales through multi proxy analyses - Magalhães, Evandro Augusto de Souza (2024)
The dynamics of amazon mangroves in the Marapanim-PA region over the last ~1524 cal yr BP have been substantially influenced by autogenic and allogenic processes, identified at millennial, secular, and decadal scales, determined through the integration of stratigraphic (radiography, granulometry, color, and facies), geochemical (XRF), isotopic and elemental data (13C, 15N, TOC, TN, C/N ratio, 13C x C/N and 15N x 13C binaries), palynological, and geochronological data (radiocarbon dating), along with orbital and drone remote sensing. Remote sensing analysis revealed that autogenic processes, such as tidal channel dynamics and the formation and erosion of muddy substrates, significantly impacted the expansion and contraction dynamics of mangroves in the Marapanim river\'s estuarine plain on a decadal scale. Paleoecological analyses suggest the initial establishment of mangroves in tidal plains areas formed by autogenic processes since at least ~1524 cal yr BP. During the Medieval Climate Anomaly (MCA) (1250 750 cal yr BP), with likely reductions in precipitation and river discharge, herbaceous vegetation with mangroves predominated in the tidal plain. It was observed that trees of genus Rhizophora were replaced by Avicennia in response to the increased salinity of the substrate during periods when this climatic event was more pronounced. The increase in precipitation and river discharges during the Little Ice Age (LIA) (500 100 cal yr BP) allowed floodplain vegetation to expand over the mangroves, likely due to reduced tidal salinity in the region. From 1850 AD (~100 cal yr BP), an increase in marine influence created favorable conditions for the development and expansion of mangroves in the studied area. Autogenic processes, identified as the main forces behind the changes observed on a decadal scale through the formation and erosion of tidal plain areas conducive to mangrove development, and allogenic processes, mainly recorded on secular and millennial scales and associated with variations in marine influence, changes in the hydrological cycle, and river discharge resulting from climatic changes, are the main forces modulating vegetation dynamics in the studied area.